Pelatihan Melaksanakan Konseling Kelompok dengan Pendekatan Realitas pada Guru BK - Sofah, Rahmi; Dewi, Ratna Sari; Razzaqyah, Fadhlina; Nurwisma, Nurwisma; Silvia, Silvia (Universitas Negeri Padang, 2022)
This community service is aimed to provide guidance and counseling teachers with understanding and skills in implementing group counseling services with a realistic approach. The target of this training is a group of musyawarah guru BK (MGBK) in Inderalaya Ogan Ilir, namely guidance and counseling teachers for junior high school, senior high school, and vocational high, totaling 24 people. This training was carried out online with some activities: material presentation, discussion, question and answer, simulation, Reflecting and Sharing Experience, using the zoom meeting application, and mentoring from guidance and counseling teachers in carrying out group counseling with a realistic approach using WhatsApp. To find out the guidance and counseling teacher's understanding of the material that has been presented by the service team, participants are given a test conducted through the google form application, and to determine the skills of guidance and counseling teachers in conducting counseling with a realistic approach, it was done through simulations using the zoom meeting application, participants acted as counselors were observed using the observation sheet. The evaluation results show that about 87% of guidance and counseling teachers understand the group counseling material with a realistic approach, and there are 73% of guidance and counseling teachers who are skilled in implementing group counseling skills with a realistic approach.